1988
DOI: 10.1021/bi00421a007
|View full text |Cite
|
Sign up to set email alerts
|

Substrate flux through methylenetetrahydrofolate dehydrogenase: predicted effects of the concentration of methylenetetrahydrofolate on its partitioning into pathways leading to nucleotide biosynthesis or methionine regeneration

Abstract: Folic acid exists in mammalian cells with a poly-gamma-glutamate tail that may regulate the flux of folates through the various cellular pathways. The substrate polyglutamate specificity of methylenetetrahydrofolate dehydrogenase from pig liver has been examined by using a competitive method and measuring apparent tritium kinetic isotope effects on Vmax/Km for methylenetetrahydrofolate. This competitive method yields very accurate ratios of Km values for alternate substrates of an enzyme and may also be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 22 publications
1
44
0
1
Order By: Relevance
“…While it might be thought that folate deficiency would affect all components of the folate pool equally, studies on the in vitro catalytic properties of the enzymes that compete for methylenetetrahydrofolate have suggested that methylenetetrahydrofolate reductase has a much lower Michaelis constant (K m ) for this substrate than thymidylate synthase or methylenetetrahydrofolate dehydrogenase (21), which would be expected to result in methyl trapping. Thus embryos with folate deficiency and those with reduced methionine synthase activity may share a propensity for apoptosis due to insufficient supplies of 10-formyltetrahydrofolate and methylenetetrahydrofolate.…”
Section: Embryonic Lethalitymentioning
confidence: 99%
“…While it might be thought that folate deficiency would affect all components of the folate pool equally, studies on the in vitro catalytic properties of the enzymes that compete for methylenetetrahydrofolate have suggested that methylenetetrahydrofolate reductase has a much lower Michaelis constant (K m ) for this substrate than thymidylate synthase or methylenetetrahydrofolate dehydrogenase (21), which would be expected to result in methyl trapping. Thus embryos with folate deficiency and those with reduced methionine synthase activity may share a propensity for apoptosis due to insufficient supplies of 10-formyltetrahydrofolate and methylenetetrahydrofolate.…”
Section: Embryonic Lethalitymentioning
confidence: 99%
“…Kinetic studies suggest that interaction of the poly-g-glutamyl tail of the methylene-tetrahydrofolate molecule with the enzyme provides binding energy and affinity for the substrate, while allowing dynamic motion and kinetic channeling of the reactive methenylpterin ring system between dehydrogenase and cyclohydrolase active sites~Cohen & MacKenzie, 1978;Wasserman et al, 1983;Green et al, 1988;Hum & MacKenzie, 1991;Pelletier & MacKenzie, 1995!. Inspection of the surface of the E. coli dph0cyc revealed that there are two significant regions of positive-charged residues, one at each end of the cleft between the two a0b domains of deh0cyc.…”
Section: Putative Methylene-tetrahydrofolate Binding Sitementioning
confidence: 99%
“…The MTHFR-catalyzed reaction commits one-carbon units to the methionine cycle ( Fig. 1) (13). Both reactions are essentially irreversible in vivo (10).…”
mentioning
confidence: 99%
“…Metabolic labeling studies, in vitro binding experiments, and mathematical modeling have indicated that methylene-THF is preferentially directed toward methionine synthesis relative to thymi-* This work was supported by Public Health Service Grant DK58144. The costs dylate biosynthesis (13,14). There is increasing evidence that the partitioning of methylene-THF between methionine and thymidylate synthesis is central to the origin of folate-related pathologies.…”
mentioning
confidence: 99%